Scientific Creativity in TVET Product Design: Integrating Scientific Knowledge and Imagination - Suradin, Salwa; Rasul, Mohamad Sattar; Omar, Marlissa; Ab. Hamid, Norzaharah; Nik Othman, Nik Norlaili Jamilah (Journal of Technical Education and Training, 2025)
Technical and Vocational Education and Training (TVET) faces a pressing need to adapt its curriculum to the demands of Industry 4.0, particularly in product design. While creativity is recognized as a crucial skill, there remains a gap in the literature regarding validating instruments for measuring scientific creativity in this context. This study aims to address this gap by developing and validating an instrument to measure scientific creativity by integrating scientific knowledge and imagination in product design for TVET teachers in Malaysia. The instrument was then subjected to content validation by eight experts. The item content validity index (I-CVI) and the scale content validity index (S-CVI) were used to determine content validity. Findings indicate strong content validity for both constructs and scientific creativity with high levels of agreement among experts. The item’s content validity index (I-CVI) ranged from 0.99 to 0.96 and the scale content validity index (S-CVI/AV) for each construct was 0.99 for the scientific knowledge construct, and 0.96 for the imagination construct. This range is valid and appropriate for developing the instruments. However, some items required refinement to enhance content validity further. This study contributes to the literature by providing a reliable instrument developed to the specific needs of TVET teachers in Malaysia, thereby filling a critical gap in the assessment of scientific creativity in product design.